Delmar's agriscience dictionary with searchable Cd-ROM - Herren, Ray V. (Delmar, 1999)
Delmar’s Agriscience Dictionary with Searchable CD-ROM is the ideal source to keep abreast of terminology in an ever-changing industry! A unique feature is the searchable CD-ROM which contains the same terms and definitions as the print dictionary